2022
DOI: 10.1016/j.cmi.2021.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of point-of-care tests in acute community-acquired lower respiratory tract infections. A systematic review and meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 33 publications
1
44
0
3
Order By: Relevance
“…The main benefits of these assays is that they are portable, miniaturized, low cost and highly integrated POC devices [57]. In the move to a new paradigm of personalized medicine, POC diagnostic testing has been proposed to improve the quality of antibiotic prescription [58] but accuracy is variable and settings need careful adjustment [59].…”
Section: Appropriate Sample and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The main benefits of these assays is that they are portable, miniaturized, low cost and highly integrated POC devices [57]. In the move to a new paradigm of personalized medicine, POC diagnostic testing has been proposed to improve the quality of antibiotic prescription [58] but accuracy is variable and settings need careful adjustment [59].…”
Section: Appropriate Sample and Methodologymentioning
confidence: 99%
“…Depending on the clinical setting and accessibility, the plain chest radiograph is not always required for diagnosis, nevertheless it still remains a relevant tool. Lung ultrasound has shown better accuracy than chest X-ray for bacterial pneumonia in emergency departments [18] and an advance during the pandemic has been its increased use for both diagnosis and follow-up [19]. The additional value of computed tomography has been widely recognized for COVID-19 pneumonia [20].…”
Section: Advances In Syndromic Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…At present, the diagnosis of CAP mainly depends on the clinical manifestations of patients, chest radiography, and the pathogen detection of respiratory secretions. 4 We hope that there are other aids to diagnose pediatric CAP on the basis of routine diagnosis and treatment. Currently, part of the studies suggest that have shown that the vitamin levels in CAP patients have a certain relationship with the treatment and prevention of the disease.…”
Section: Introductionmentioning
confidence: 99%